2016
DOI: 10.1080/09168451.2015.1136882
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in the glucose content of dilute sulfuric acid–pretreated rice straw liquid hydrolysates: implications for bioethanol production

Abstract: Rice straw is a promising resource for bioethanol production. Because the glucose content of pretreatment liquid hydrolysates is highly correlated with ethanol yield, the selection of appropriate rice cultivars is essential. The glucose content in liquid hydrolysates of pretreated rice straws of 208 diverse cultivars was evaluated in natural field in 2013 and 2014 using a novel high-throughput system. The glucose content of the rice straw samples varied across cultivars and was affected by environmental factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Biotechnology, andBiochemistry, 75, 1104-1112. rice straw after dilute acid pretreatment using these cultivars were also very high (Goda et al, 2016;Teramura et al, 2013). However, as observed in CRCT overexpression lines, the grain yield of these rice cultivars was significantly low because of their small panicles (Matsushita et al, 2011).…”
Section: Disclosure Statementmentioning
confidence: 68%
See 1 more Smart Citation
“…Biotechnology, andBiochemistry, 75, 1104-1112. rice straw after dilute acid pretreatment using these cultivars were also very high (Goda et al, 2016;Teramura et al, 2013). However, as observed in CRCT overexpression lines, the grain yield of these rice cultivars was significantly low because of their small panicles (Matsushita et al, 2011).…”
Section: Disclosure Statementmentioning
confidence: 68%
“…In (2013) reported that glucose contents in liquid hydrolyzate of rice straw was varied depending on cultivars and ranged from 5.0 to 24.5 g per 100 g DW among 13 rice cultivars in Japan. Recently, Goda et al (2016) reported more thorough research of glucose contents in liquid hydrolyzate from straws using 208 rice cultivars that there were significant variations in glucose contents among rice cultivar and the glucose content of rice cultivar 'Tachisuzuka' was the highest among 208 rice cultivars showing 23 g per 100 g DW. Calculating from the result of Figure 1, CRCT overexpression lines showed markedly higher glucose contents in liquid hydrolyzate of straw that the glucose contents in liquid hydrolyzate of CRCT overexpression lines were amounted to 23.7-29.1 g per 100 g DW.…”
Section: Effects Of Crct Expression Levels On Glucose Content In Liqumentioning
confidence: 99%
“…In our previous study, the expressions of starch synthesis–related genes such as OsGPT2 , OsAGPL1 , OsAGPS1 , OsBEI and OsPho1 were highly correlated with the expression of CRCT in the leaf sheath of CRCT overexpression lines and knockdown lines (Morita et al, 2015; Morita et al, 2019). There are considerable differences in the starch content in the leaf sheath among rice varieties (Goda et al, 2016). Thus, in this study, the relationships between the expression levels of CRCT and the starch synthesis–related genes were analysed in the six rice cultivars, Nipponbare, Koshihikari, Habataki, Takanari, Momiroman and Leafstar (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, the expressions of starch synthesis-related genes such as OsGPT2, OsAGPL1, OsAGPS1, OsBEI and OsPho1 were highly correlated with the expression of CRCT in the leaf sheath of CRCT overexpression lines and knockdown lines (Morita et al, 2015;Morita et al, 2019). There are considerable differences in the starch content in the leaf sheath among rice varieties (Goda et al, 2016).…”
Section: Expression Of Starch Synthesis-related Genesmentioning
confidence: 87%
“…In our previous study, the expressions of starch synthesis-related genes such as OsGPT2 , OsAGPL1 , OsAGPS1 , OsBEI andOsPho1 were highly correlated with the expression of CRCT in the leaf sheath of CRCT overexpression lines and knockdown lines (Morita et al, 2015;Morita et al, 2019). There are considerable differences in the starch content in the leaf sheath among rice varieties (Goda et al, 2016). Thus, in this study, the relationships between the expression levels of CRCT and the starch synthesis-related genes were analyzed in the six rice cultivars, Nipponbare, Koshihikari, Habataki, Takanari, Momiroman and Leafstar (Figure 1).…”
Section: Expression Of Starch Synthesis-related Genesmentioning
confidence: 89%